(3JMOjGJ GdJcGed GdGbJUGOj GdYQHj aj YUQ GdYhdeI (B/s - (3GdfOhj, eMSfs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2011)
(3GdGWGQ GdJGQjNj h GdbGfhfj ddJcGed GdGbJUGOj GdOhdj h GdGbdjej , eaghe GdJcGed GdGbJUGOj GdOhdj h eSGQ gPG GdJWhQ , GdJMOjGJ GdOhdjI h GdGbdjejI ddJcGed GdGbJUGOj GdYQHj , GdJLGQH GdGbdjejI GdYQHjjI aj GdJcGed GdGbJUGOj , feGPL ef GdJLGQH GdGbdjejI ZjQ GdYQHjI aj GdJcGed GdGbJUGOj(B: (3eLdS GdJYGhf GdNdjLj , GJMGO GdeZQH GdYQHj , feGPL ef GdJLGQH GdGbdjejI ZjQ GdYQHjI aj GdJcGed GdGbJUGOj (B: (3GdGJMGO GdGhQhHj h QGHWI Ohd LfhH TQb BSjG (BASEAN .s
(3eQGLY U(B.373 (3; edGMb U(B.363s
Keywords: (3GdGbJUGOs; (3GdJcGed GdEbJUGOjs; (3GdShb GdYQHjI GdeTJQcIs